Cavitation effects on textured compression rings in mixed lubrication. (31st May 2016) - Zavos, Anastasios; Nikolakopoulos, Pantelis G.
Abstract: Thin lubricant films and cavitation to ring–bore contact have a directly correlation between wear and emissions output of internal combustion engines. Thus, there is a need to develop innovate engineering solutions such as surface texturing. In particular, micro textures are manufactured in order to keep more lubricant in weakly lubricated contact. An isothermal mixed‐hydrodynamic analysis was developed for textured compression rings, which utilised the effects of two‐phase flow using Navier–Stokes equations, vapour transport and asperity interaction. Realistic boundary conditions are used from a real motorbike engine. This paper employs a computational model including multiphase flow of the ring–bore conjunction in order to predict the effects of surface texturing of the barrel face ring around the dead centres. The model is validated using numerical and experimental results from the literature. Additionally, flow simulations have been performed, on how micro‐dimples shape and depth on the ring liner affect on the total friction and minimum lubricant film. Copyright © 2016 John Wiley & Sons, Ltd.